2021
DOI: 10.1002/vms3.478
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high dietary energy on obesity and oxidative stress in domestic pigeons

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Blood biochemical parameters are reliable indicators of the well‐being of birds and reflect the nutritional, physiological and pathological status of birds’ body (Kraus et al., 2021 ). Thus, some serum indices provide clinical information for diagnosis and characterization of avian diseases (Hosseinian and Hasanzade, 2021 ; Li et al., 2017 ). As mentioned below, high ambient temperature causes several changes in the physiological status and blood biochemical profile in broilers (Wasti et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Blood biochemical parameters are reliable indicators of the well‐being of birds and reflect the nutritional, physiological and pathological status of birds’ body (Kraus et al., 2021 ). Thus, some serum indices provide clinical information for diagnosis and characterization of avian diseases (Hosseinian and Hasanzade, 2021 ; Li et al., 2017 ). As mentioned below, high ambient temperature causes several changes in the physiological status and blood biochemical profile in broilers (Wasti et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intake of HE density diet has been recognized as one of the important causes of oxidative stress in animals such as pigeons (Hosseinian and Hasanzadeh, 2021), piglets (Adebowale et al, 2015), rats (Jiang and Jiang, 2018), cows (Wang et al, 2010), and sheep (Liang et al, 2020). This current study revealed that energy level and FA have no effect on plasma and breast muscle MDA and SOD levels in broiler chickens.…”
Section: Discussionmentioning
confidence: 45%
“…Our evidence supports a previous study by Cetin et al (2019), who observed that plasma MDA was not influenced by increasing dietary energy levels. The recent study by Hosseinian and Hasanzadeh, (2021) No previous studies involved the effect of HE diet on breast muscle MDA and SOD, so we could not compare our results in this aspect.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Sunflower seeds are one of the most popular foods to supply bird feeders. The seeds contain at least 40-50% fat, and this food is termed a high-energy diet for birds [60]. Birds have a fast metabolism, meaning that they can burn calories quickly.…”
Section: Discussionmentioning
confidence: 99%